Evaluation of safed musH (Chlorophytum borivilianum Santapau & Fernandes) germplasm - Singh, S K Kothari, K (Journal of Spices and Aromatic Crops, 2001)
Safed musU (Ch 10 rophy tum borivilianum Santapau & Fernandes), an herbaceous plant belonging to the family liliaceae is mostly collected from wild sources as its tubers are in high demand in indigenous systems of medicine in the preparation of a aphrodesiac drug for curing general debility. Safed musH germplasm were evaluated for their performance. A large variability was observed in terms of morphological and yield attributing characters and tuber yield among the germplasm. CB/MS-6 gave highest number of leaves planrl (23.S), number of tubers planrl (10.2), tuber thickness (0.80 cm) and fresh (65.3 g planrl) and dry (S.5 g plant-I) tuber yield. Further, two distinct plant types (prostrate or spreading and erect) were observed among these accessions. Observations on the crop grown in farmer’s field in different locations revealed the feasibility of its cultivation in semi arid areas of Andhra Pradesh, Madhya Pradesh and Maharashtra.